Improving the Management of Diabetes in a Secure Forensic Psychiatric Setting in the UK - Raymond Effah; Maria Coppel; Christopher Lawrence (BJPsych Open)
Aims: To measure the quality of care given to diabetic patients while admitted to a secure forensic setting. Across psychiatric services, individuals with a serious mental illness have higher rates of diabetes compared with the general population. Patients in forensic inpatient services often have long lengths of stay in hospital which should allow optimisation of diabetes management. We hypothesise that despite intervention, standards in diabetic management are not met.